Spatial patterns of cryptobenthic coral-reef fishes in the Red Sea - Coker, D.; Di Battista, Joseph; Sinclair-Taylor, T.; Berumen, M. (Springer Verlag, 2017)
Surveys to document coral-reef fish assemblages are often limited to visually conspicuous species, thus excluding a significant proportion of the biodiversity. Through standardized collections of cryptobenthic reef fishes in the central and southern Red Sea, a total of 238 species and operational taxonomic units (OTUs) from 35 families were collected. Abundance and species richness increased by 60 and 30%, respectively, from north to south, and fish community composition differed between the two regions and with proximity to shore in the central region. Models suggest regional influences in fish communities, with latitudinal patterns influenced by key coral groups (Acropora, Pocilloporidae) and variation in environmental parameters (chlorophyll a, sea surface temperature, salinity). This study illustrates the limited taxonomic resolution in this group and in this region, and the need to expand baseline data for this under-studied assemblage. To assist in advancing this initiative, we have produced a catalogue of specimens, archived photographs, and established a DNA sequence library based on cytochrome-c oxidase subunit-I barcodes for all OTUs.